THE CONCEPT OF FRIENDSHIP AND ITS LINGUOCULTURAL FEATURES IN UZBEK AND ENGLISH LANGUAGES - G. K. Soatova (Modern American Journals, 2025)
This research explores the concept of friendship and its particular linguistic and cultural features in Uzbek and English. Friendship exists as a universal human bond that is influenced by social values, historical context, culture, language, and varies between different societies. This paper seeks to analyse “friendship” through proverbs and idioms from both cultures, exploring its meaning and usage, emphasising the individualistic traits of English culture juxtaposed with the collectivist nature dominant in Uzbek culture regarding perception, formation, and maintenance of friendships. Additionally, it highlights distinctive cultural boundaries such as specific words or phrases that mark these differences, which reveal possibilities of difficulty in intercultural communication concerning friendship, along with approaches to overcome them.
Keywords: Friend, friendship, comparison, differences, collectivism, mutual understanding, betrayal, linguistic differences.